Patient-reported outcome measures (PROMs) in pancreatic cancer: a systematic review. Issue 2 (February 2020) - Maharaj, Ashika D.; Samoborec, Stella; Evans, Sue M.; Zalcberg, John; Neale, Rachel E.; Goldstein, David; Merrett, Neil; White, Kate; Croagh, Daniel; Pilgrim, Charles H.C.; Evans, Peter; Knowles, Brett; et al.
Abstract: Background: The aim of this systematic review is to examine patient-reported outcome measures (PROMs), their attributes and application in patients with pancreatic cancer (PC). Method: A systematic literature search was undertaken of articles published to June 2018 to identify PROMs applied in primary studies in PC. Characteristics of the included studies and PROMs were described with identified scales grouped into five domains. The psychometric properties of the identified PROMs were further assessed for reliability and validity among patients with PC. Results: From 1688 studies screened, 170 were included. Almost half (48%) were conducted in patients with unresectable PC; the majority of these (68%) were evaluated in randomized controlled trials. Median questionnaire completion rates fell below 10% of the original cohort within 12 months in patients with unresectable PC compared to 75% in patients with resectable PC. Seventy PROMs were identified, 32 measuring unidimensional parameters (e.g. pain) and 35 measuring multidimensional (e.g. quality of life) constructs. Only five (7%) PROMs were disease-specific and 13 (19%) were validated in patients with PC. Fifty scales were grouped into 19 physical, 9 psychological, 6 psychiatric, 9 social and 7 other domains. Conclusion: Three multidimensional PROMs, the: (i) FACT-HEP in unresectable PC; (ii) QLQ-PAN26 (in conjunction with its core QLQ-C30 PROM) in resectable PC; and (iii) MDASI-GI are recommended as instruments to capture quality of life in patients with PC. Summarised scales and psychometric evaluation provide a framework to choose PROMs for scales not captured by the recommended PROMs.